Dynamic action of keratinase on wool fibre tracked by FITC-labelled enzyme. Issue 3 (4th May 2021) - Cao, Zhang-Jun; Song, Xiao-Xiao; Zhu, Qian; Wang, Juan; Gong, Run; Zhang, Yun-Long; Wang, Gang
Abstract: Due to pollution in the process of chemical treatments, wool textile industry has been remarkably changed to use eco-friendly reagents in preparatory and finishing operations. We previously isolated a wool-degrading bacterial strain ( Pseudomonas sp.3096-4) from decomposed wool fabrics, which produces a new type of keratinase capable of degrading cuticle layers. In this study, using fluorescein isothiocyanate (FITC) labelling and scanning electron microscope, we found that the Pseudomonas -derived keratinase efficiently removed the cuticle layer by protein hydrolysis and the degradation proceeded from surface to inner components of wool fibres. A 48-h treatment with the keratinase effectively removed cuticle scales on the wool surface with interior structure largely intact. This treatment significantly reinforced the strength and tenacity of wool fibres, showing its potential as a promising method in the wool textile industry.